2010
DOI: 10.1088/0954-3899/37/4/045005
|View full text |Cite
|
Sign up to set email alerts
|

Understanding thee+eD(*) +D(*) −processes observed by Belle

Abstract: We calculate the production cross sections for D * + D * − , D + D * − and D + D − in e + e − annihilation through one virtual photon in the framework of perturbative QCD with constituent quarks. The calculated cross sections for D * + D * − and D + D * − production are roughly in agreement with the recent Belle data. The helicity decomposition for D * meson production is also calculated. The fraction of the D * ± L D * ∓ T final state in e + e − → D * + D * − process is found to be 65%. The fraction of DD * T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…2. A comparison of numerical results of the two-photon mechanism of electron-positron annihilation with the one-photon mechanism shows that the two-photon contribution to the total cross sections for the production of a pair is suppressed by a small factor 10 −3 , which is associated with the ratio of interaction constants α 2 /α 2 s and qualitatively corresponds to the results for D + D − [55]. There are no factors that could lead to an increase in the cross sections for two-photon annihilation compared with one-photon annihilation.…”
Section: Numerical Results and Conclusionsupporting
confidence: 62%
“…2. A comparison of numerical results of the two-photon mechanism of electron-positron annihilation with the one-photon mechanism shows that the two-photon contribution to the total cross sections for the production of a pair is suppressed by a small factor 10 −3 , which is associated with the ratio of interaction constants α 2 /α 2 s and qualitatively corresponds to the results for D + D − [55]. There are no factors that could lead to an increase in the cross sections for two-photon annihilation compared with one-photon annihilation.…”
Section: Numerical Results and Conclusionsupporting
confidence: 62%
“…On the other hand, although modeling the B meson LCDA as Φ B (x) = f B 2 √ 2Nc δ(x − x 0 ) may seem to be a overly rough approximation, it may arguably capture some reasonable physics provided that m u is taken as the constituent quark mass of order Λ QCD . That is, this approximation is compatible 12 For a phenomenological investigation of time-like D ( * )+ D ( * )− form factor from this perspective, see [43].…”
Section: Asymptotic Behavior Of Heavy-light Meson Em Form Factormentioning
confidence: 79%
“…(E)-4-((2-hydroxyphenyl)diazenyl)-3-phenyl-1H-pyrazol-5(4H)-one, HL, and its Ni(II), Pd(II) and Pt(II) complexes were synthesized and the biological activity was evaluated for antitumor, antioxidant and antimicrobial activity as well as DNA cleavage. Their structures were assigned depending on the elemental analysis, conductivity, magnetic moment, spectral measurements (IR, 1 HNMR, mass and UV-Vis) and thermal analysis. 3D molecular modeling using DFT method confirmed that the geometrical structures agree well with the suggested experimental ones.…”
mentioning
confidence: 99%
“…The compounds having pyrazolone moiety are found to be remarkable anti-tubercular, anti-inflammatory, antibacterial, antifungal and antitumor activity. [1] Due to the reactivity of position −4 in the pyrazolone ring, it undergoes a coupling reaction with a number of aryl diazonium chlorides forming 4-arylazo derivatives, which considered an important class of azo dyes. The azo-derivatives of pyrazolone compounds have attracted attention because of their potential importance in medicinal chemistry as antimicrobial and therapeutic agents, [2] in analytical chemistry as complexing agents having an excellent ability to form chelates with a number of metal cations [3] for the determination of these metal ions spectrophotometrically [4] , and in industrial chemistry as dyestuffs.…”
mentioning
confidence: 99%